Upholding Democracy Between Indonesia and South Korea In The Presidential Impeachment Mechanism From The Perspective Siyasah Dusturiyah - Ma'luf, Muhammad Alif; Pelita, Bobang Noorisnan; Rizal, Lutfi Fahrul (KRTHA BHAYANGKARA, 2025)
Marriage This study aims to analyze and compare the mechanisms of presidential impeachment in Indonesia and South Korea in the perspective of democratic theory and siyasah dusturiyah. Although both countries embrace democracy and presidentialism, there are significant differences in the legal procedures and institutional configurations involved in impeaching the head of state. A juridical-normative approach is used with descriptive-analytical and comparative methods, accompanied by theoretical reviews from Robert A. Dahl, Larry Diamond, and Fareed Zakaria, as well as a review of political Islamic values from figures such as al-Mawardi, Ibn Taymiyyah, and al-Ghazali. The findings show that the impeachment mechanism in South Korea is more juridical and final, while Indonesia is more political and layered. From the perspective of siyasah dusturiyah, this mechanism can be seen as a modern manifestation of the principles of al-'azl, maslahah, and sadd al-dzari'ah. This study concludes that the effectiveness of impeachment in upholding democracy and justice is strongly influenced by institutional integrity and orientation towards public good, not merely formal procedures.